Pornography in Diversity: A Study of the MUI’s Fatwa on Pornography - Novelia Musda (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2013)
Pornography has been one of the most controversial issues among Indonesian over decades. This article explores Indonesian Muslim views and conceptions of pornography by examining MUI’s (Indonesian Ulama Council) fatwa. In a plural society like Indonesia, Muslims have used an Islamic perspective to the scope and meanings of pornography in order to support the government plan to issue the porn bill (RUU Anti-Pornografi). The author argues that religious and cultural diversities in Indonesia have challenged Muslim discourse about pornography, partly because local culture and customary laws in certain regions of Indonesia hold different views in defining what pornography is. In a broader context, this article suggests that religion has become increasingly influential to pattern of state’s discourse about pornography and the porn bill. Keywords: pornography, fatwa, MUI, Islamic law.